Computational fluid dynamic simulation modeling of carbon capture using polyethylenimine impregnated protonated titanate nanotubes - Hyoung‐Chul Kim; Hongbo Du; Raghava R. Kommalapati; Ziaul Huque; Xinhua Shen (Energy Science & Engineering, 2020)
Abstract A comprehensive computational fluid dynamic (CFD) model of CEES‐developed polyethylenimine impregnated protonated titanate nanotubes (PEI‐PTNTs) was developed using the Multiphase Flow with Interphase eXchanges (MFiX) package to evaluate the performance of the PEI‐PTNTs in a 1‐MW pilot‐scale carbon capture reactor developed by the National Energy Technology Laboratory (NETL). In this CFD model, the momentum, continuity, and energy transport equations were integrated with the first‐order chemistry model for chemical kinetics of heterogeneous reactions to predict the adsorption of CO2 onto amine‐based sorbent particles and the reactor temperature. Based on the amount of the CO2 adsorption obtained in the small‐scale experiment, the coefficients for the chemical reaction equations of PEI‐PTNTs are adjusted. The adjusted PEI‐PTNTs model is applied to the simplified numerical model of 1‐MW pilot‐scale carbon capture system, which is calibrated through the comparison between our simulation results and the results provided by NETL. This calibrated CFD model is used for selecting the optimized flow rate of the gas phase. Our study shows that the optimized gas flow rate to absorb 100% CO2 without loss is 1.5 kg/s, but if higher absorption rate is preferable despite some loss of CO2 absorption in the reactor, a higher flow rate than 1.5 kg/s can be selected.